HarpyGame: um jogo sério customizável com interface multimodal para reabilitação de indivíduos pós-AVE - Cyrino, Gabriel Fernandes (2019)
Stroke is the most common disease that leads to the dexterity impairment of the upper limbs. To provide a better quality of life, patients must submit to therapeutic resources that focus on the gain of muscle activity. In fact, rehabilitation must be precocious, intensive and repetitive, which leads to the challenge of how to maintain patient motivation and dedication. In this context, serious games have emerged as an advantageous and enjoyable alternative to rehabilitation treatment, when compared to traditional therapies. However, most serious games are limited to simple 2D environments or low-quality 3D environments, which can affect patient interest and engagement. Moreover, in many of these games, it is not possible to adapt the rehabilitation tasks, according to the patient clinical stage. Thus, this work presents the development of a customizable serious game, based on Virtual Reality techniques to achieve a more natural and intuitive interface. Besides, since each patient has his own limitation, the game was developed to allow different types of input devices. In so doing, the system was designed considering four intercommunicable layers: 1) A control panel, responsible for the control and customization of the game, registration of patients and generation of comparative reports; 2) A serious game that presents an environment with realistic graphics, containing levels and adaptive tasks; 3) A database that maintains information such as patient profiles, game settings, goals and challenges achieved; 4) And a multimodal interface that allows the use of input devices such as Myo, Joysticks and an assisted support platform in order to provide the suitability of different patient profiles in the game. The research considered the assistance of physiotherapists to provide protocols that the game followed. Results indicated significant acceptance by the patients, implying the system's potential use in the post-stroke rehabilitation process of the upper limbs.